Heterogeneidade espacial e temporal de variáveis limnológicas no reservatório de Itupararanga associadas com o uso do solo na Bacia do Alto Sorocaba-SP - Frascareli, Daniele [UNESP]; de Souza Beghelli, Frederico Guilherme; da Silva, Sheila Cardoso; Carlos, Viviane Moschini [UNESP] (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2015)
Among the human activities around waterbodies, pollution by runoff of agrochemicals. and sewage discharges into waterbodies can cause nutrient loading, which contributes to the eutrophication process and degradation of these ecosystems. This work aimed to determine spatial and seasonal heterogeneity in surface waters of the Itupararanga Reservoir and analyzed the influence of land use on the reservoir water quality. The reservoir is used for water public supply and is located in Ibiúna City, São Paulo, Brazil. Trophic State Index (TSI) and limnological variables were analyzed in both the wet and dry seasons in 2013. Data were compared with land use maps and with Brazilian environmental legislation-CONAMA n° 357/2005. The results indicated that total phosphorus was not in compliance with the CONAMA standard. The reservoir showed spatial and seasonal heterogeneity for TSI and also for limnological variables. Spatial heterogeneity was demonstrated using cluster analysis of water quality and land use data. The cluster analysis indicated that forest cover is an important factor in preventing solids from entering into the system. It also indicated that agriculture practices around the Itupararanga Reservoir are the main sources of nitrogen, whereas tributaries are responsible for the major phosphorus inputs. Since the Itupararanga Reservoir is socially and economically important to the region, conservation and preservation measures are recommended in order to mitigate harmful activities to the aquatic environment.
Spatial and seasonal heterogeneity of limnological variables in itupararanga reservoir associated with the land use in the bacia do alto sorocaba-sp
Keywords: Eutrophication; Heterogeneity; Water quality